The influence of entrepreneurial values on export intention of small medium enterprises in Malaysia / Looi Kim Hoe - Looi , Kim Hoe (2016)
A good understanding of small and medium-sized entrepreneurs’ motivations for export becomes imperative for the achievement of High Impact Programme - Going Export under the Malaysian Small and Medium-sized Enterprises Masterplan (2012 – 2020). Research has demonstrated that systematic study of values can generate insights about entrepreneurial behaviour. Values are often linked to entrepreneurial intention but to date, a detailed, well-developed and empirically tested model from values to entrepreneurial intention is missing. Extant literature also suggests that it is critical for future research to account for the context within which international entrepreneurship occurs. There are several objectives for this study. The first objective is to propose and empirically test a theory-driven research framework that coherently integrates entrepreneurial values and the Theory of Planned Behaviour in the context of small and medium-sized international entrepreneurship. The second objective is to identify entrepreneurial values that significantly influence the three determinants of export intention, i.e. Behavioural Beliefs, Normative Beliefs and Control Beliefs. The third objective is to investigate the significance of the three antecedents of intention in predicting export intention in a collectivist country. The fourth objective is to determine the relative weightage of the three antecedents of intention in predicting Export Intention in a collectivist country. The fifth objective is to test the moderation effect of observed heterogeneity (i.e. gender, ethnicity, current exporting status of entrepreneurs) as well as unobserved heterogeneity on the integrative framework. The final objective is to provide insights to fine tune public policies that aim to facilitate a greater level of exporting by SME entrepreneurs and further the economic progress of Malaysia. This is a post-positivist and cross-sectional study conducted via survey questionnaire on 243 small and medium-sized entrepreneurs in Malaysia. Data were analysed using Structural Equation Modelling techniques (AMOS and Partial Least Squares). The results revealed that this integration is supported by data and therefore, extended the theory of entrepreneurship about the impact of entrepreneurial values on entrepreneurial intention. Self-direction and Stimulation values significantly influence the antecedents of Export Intention. Besides this, Behavioural Belief Strength is a stronger predictor of export intention than Control Belief Strength. The group-specific Partial Least Squares results enhanced the overall explanatory power of the integrated model. In other words, the motivations from entrepreneurial values to export intention are moderated by observed heterogeneity and unobserved heterogeneity. Some structural paths are not generalizable across observed heterogeneity, which mean that there are some differences between the two groups. Overall, this integration of entrepreneurial values and the Theory of Planned Behaviour significantly enhances the understanding of the causal relationship between small and medium-sized entrepreneurs’ values and export intention. Moreover, the results demonstrate that an aggregate-level of analysis can be misleading. From analysis by observed and unobserved heterogeneity, this study adds to the body of knowledge about human variations in behaviour and the associated reasons; hence, the academic community becomes more enlightened and ‘worldly’. The significant theoretical contributions to the international entrepreneurship literature from this study are in international entrepreneurship theory, multi-disciplinary integration and intra-national diversity. This study is evaluated against two influential articles in terms of Theoretical Contributions and Contextualizing Theory Building in Entrepreneurship Research. The results from both evaluations are satisfactory.